Fetal demise and failed antibody therapy during Zika virus infection of pregnant macaques - Diogo M. Magnani (Nature Portfolio, 2018)
Zika virus (ZIKV) infection in pregnant women has been associated with fetal developmental defects. Here, the authors show that a Brazilian ZIKV isolate causes fetal demise in non-human primates and that antibody treatment at time of peak viremia is insufficient to clear ZIKV replication from amniotic fluid.